Sustainability in IT education: A game-based approach - Benedicte H. Gangstø; Monica Divitini (Interaction Design and Architecture(s))
Information Technology (IT) has a critical role in supporting sustainable development. However, there are also various ways in which IT contributes negatively to it. Despite the ever-growing need for IT professionals qualified to take on these challenges, education in sustainability and IT has so far been lacking. IT students need an understanding of the far-reaching implications of IT, and to acknowledge their responsibility for the systems they create, to actively contribute to positive change. To address this need, our research explores how collaborative games can be utilized as a tool to develop IT students’ knowledge and perception of sustainability and its connection with IT. Previous research has found the use of games to teach sustainability promising, and in this paper, we present SustainIT, a 3D collaborative game for IT students. In SustainIT, the players communicate across the past and future to make more sustainable decisions for an IT company. The learning goals of the game are to promote systems thinking, an understanding of the connection between sustainability and IT, and to challenge existing perceptions. Focus has been put on finding effective game elements to promote learning and engagement to support these learning outcomes. In the paper we present the design and the evaluation of the game. The final prototype was evaluated by an expert in sustainability in IT education, and a group of students within the target group. The overall evaluation was positive, with the game being evaluated as relevant and interesting. However, the evaluation also pointed out some challenges with the integration of background information about sustainability into the game. Our findings can inform the development of games aimed at cultivating the understanding of the impacts of IT on sustainability.